Aeroacoustic analysis of a generic jet-fighter weapon bay at transonic mach number - Bacci, David; Saddington, Alistair J.; Hadar, Ben-Gida (American Institute of Aeronautics and Astronautics (AIAA), 2026)
Aero-acoustic analysis was conducted on the weapon bay of a generic aircraft model using frequency-based standard and high-order spectral approaches. The bay model was installed on a representative combat aircraft, incorporating doors and a store. The effect of angle of attack and store position on the aero-acoustic response within the weapon bay was analysed at a transonic Mach number of 0.90. It was found that store position and angle of attack not only influenced the appearance of the resonant mode but also the non-linear interaction, hindering in some cases the formation of harmonics and sub-harmonics of the dominant tone.